PENINGKATAN HASIL BELAJAR MATEMATIKA MELALUI MEDIA POP-UP BOOK QR CODE KELAS 4 SDN 3 KEMUDO - Putri Zudhah Ferryka; Atik Dwi Subekti; Dyah Putri Perdani; Eis Masfiroh; Eka Sri Handayani; Evi Pratiwi; Falakhatun Nurani; Fani Widia Putri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematics learning outcomes of fourth-grade students at SD N 3 Kemudo in the topic of the characteristics of plane figures. This problem is caused by teacher-centered learning, the lack of innovative learning media, and low student engagement in the learning process. This study aims to improve mathematics learning outcomes through the use of Pop-Up Book QR Code media for fourth-grade students at SD N 3 Kemudo in the 2025/2026 academic year. This study is a Classroom Action Research (CAR) conducted in three cycles: planning, action, observation, and reflection. The research subjects were 25 students, consisting of 13 boys and 12 girls. Data collection techniques were carried out through observation, tests, interviews, and documentation. Data were analyzed using quantitative and qualitative analysis techniques. The results showed that the use of Pop-Up Book QR Code media can improve students' mathematics learning outcomes. Student learning completion increased from 40% in Cycle I to 68% in Cycle II and reached 88% in Cycle III. Furthermore, student engagement, motivation, and enthusiasm in participating in learning also increased. Thus, the Pop-Up Book QR Code media is effective in improving mathematics learning outcomes in the characteristics of plane figures.